Hubungan Status Ekonomi dan Pengetahuan Ibu Dengan Sikap Ibu Dalam Melakukan Baby SPA Pada Bayi Usia 3-12 Bulan di Klinik Siti Hajar - Pasaribu, Renti Magdalena Br; Sasmartih, Rati; Sitinjak , Regina; Hia, Regina Midar Hati; Siregar, Debi Novita (Journal of Pharmaceutical and Sciences, 2025)
Background: Baby Spa or Solus Per Aqua refers to water-based therapy aimed at relaxing the body through scrubbing, massage, and infant exercises. Many mothers who have babies are not familiar with the term baby spa and do not know the techniques of doing baby spa, especially in the middle to lower class areas. Objective: This study aims to determine the relationship between economic status and maternal knowledge with the mother’s attitude in doing baby spa for babies aged 3-12 months at the Siti Hajar Clinic. Methods: This method uses quantitative research with a correlation study research design. In this study, the population in this study are all mothers who have babies aged 3-12 months at the Siti Hajar Clinic, totaling 30 people. The sample amounted to 30 respondents. The technique used for sampling is total sampling. Data collection using questionnaires. Data analysis used is univariate and bivariate analysis with Chi-Square test. Results: Based on the results of the chi-square test regarding the relationship between economic status and maternal knowledge with the mother’s attitude in doing baby spa for infants aged 3-12 months, the p-value is 0.001 (p < 0.005). Conclusion: So it will be concluded that ????0 is not accepted ????1 is accepted which means that there is a relationship between economic status and maternal knowledge with the attitude of mothers in doing baby spa for babies aged 3-12 moths at the Siti Hajar Clinic.